The analysis of bank profitability determinants in the banking sector of Azerbaijan - Ahmadov, Rufat; Yagublu, Araz; Rzayev, Javid (ADA University, 2022)
The analysis of profitability determinants for banking sector in Azerbaijan was done in this study that used bank specific and external variables and analyzed these variables for the years between 2010 and 2020. A multiple linear regression model (with a panel data) was used as an inferential tool and the following results were obtained. Firstly, bank size, capital adequacy and loan growth are significant and positive factors for bank profitability in Azerbaijan. On the contrary, credit risk, liquidity and leverage are negative for the financial performance (profitability) of banks in the country. Cost to income or cost efficiency ratio was not a significant factor for the profitability of banks. Furthermore, market share is not uniform in terms of its effect as it impacts ROA and ROE positively and significantly whereas its effect on net interest margin is not significant. Moreover, GDP growth rate was a significant and positive determinant of profitability whereas inflation was not significant despite its positive effect. Market share variable was a significant and positive for ROA and ROE whereas the same variable did not have a significant impact on net interest margin. The recommendations for the banks suggest that they have a prudent risk management policy in order to exceed borrowing capacity, have a rigorous due diligence for loans in order to reduce the proportion of non-performing loans in the future, maintain a balance between loan and deposits so that unforeseen fund requirements can be covered, expand their loan portfolio to achieve a higher growth rate and seek the accomplishment of economies of scale through centralization and efficiency enhancement. Expansion of market share could also be helpful in terms of improving ROA and ROE of banks.
Keywords: Banking sector.; Banking sector -- Azerbaijan.; Financial system.; Business